BEHAVIOR OF USE IODIUM SALT BASED ON THE EDUCATION LEVEL MOTHER IN MEGATI VILLAGE BALI PROVINCE TABANAN DISTRICT - Ni Luh Gede Dian Eka Putri; I Komang Agusjaya Mataram; I Made Purnadhibrata (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
GAKI one of the serious public health problems. One of the ways to overcome GAKI is to increase the consumption of iodized salt. the use of iodized salt by residents of Tabanan Regency has only reached 67% 80% (target). The problem in this study is how the behavior of iodized salt use and the level of formal education of housewives in Megati Village. The purpose of this study was to determine the behavior of iodized salt use based on the level of formal education of housewives in Megati Village. The population in this study were housewives in Megati Village. The sample size obtained was 90 samples with the sampling method using random sampling technique that is by random sampling. Data collected in May 2019 include primary data and secondary data with observational types with a cross sectional design. In this study, the results showed that most of the samples had a secondary education level (SMA / SMK) of 48 people (53.3%), while the sample at the level of primary education (SD - SMP) was 16 people or 17.8%. Most of the samples have a sufficient level of knowledge as many as 54 people (60%), while at the level of lack of knowledge there are 17 people (18.9%). The attitude measurement in this study most of the samples had good attitude as many as 86 people (95.6%), while in the attitude enough there were 4 people (4.4%). Samples with a high level of education have a sufficient level of knowledge as many as 14 people (15.6%) but there are also those who have less knowledge as many as 11 people (28.9%) while a sample with a basic education level has a good level of knowledge of 11 people (12.1%) but there are also who have enough knowledge as many as 5 people (5.6%). Based on the availability of consumption, it is known that as many as 4 people who consumed iodized salt in sufficient categories and from 4 samples the availability of iodized salt in sufficient categories was 1 person and less than 3 people.Keywords: Education Level, Knowledge, Attitude, Consumption Iodized Salt